Functional and conceptual approach in the development of communicative competence of law students - Irina A. Pushkareva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper discusses the formation of communicative competence of law students in practical classes in a foreign language using a functional and conceptual approach. The author identifies the leading principals of higher legal education and identifies the basic needs of law students in order to improve their professional training and select the relevant content of the discipline «Foreign language in the field of jurisprudence». Distinctive features of the functional and conceptual approach in teaching a foreign language and the effectiveness of its use for the formation of foreign language communicative competence in the professional field are taken into account. The developed structural and functional model of the formation of communicative competence has been successfully tested within the framework of the studied discipline. The control of the studied topic in the form of a step-by-step organization and role-playing game showed a high degree of assimilation of educational material by students and the ability to apply it in practice, which confirms the effectiveness of using a functional and conceptual approach in the process of forming the communicative competence of students of legal specialties.